Screening items in an aging chain with a co-flow structure: an application to the product pipeline management problem - Figueiredo, Paulo (2017)
Submitted by Núcleo de Pós-Graduação Administração (npgadm@ufba.br) on 2017-04-05T18:13:07Z No. of bitstreams: 1 Screening items in an aging chain with a co-flow structure - an application to the product pipeline management problem.pdf: 570975 bytes, checksum: f9481af6329de40a930697a83c98aacb (MD5)